Fuel Quality Monitoring System in Indonesia: case study on gasoline quality improvement. (3rd September 2010) - Hirota, Keiko
This paper advocates periodical monitoring of fuel quality for conformation to quality standards. The Fuel Quality Monitoring System (FQMS) aims to phase out off-specification fuel from the market by a government initiative. The FQMS in developing countries has rather weak management because the insufficient analytical facilities and unskilled human resources result in inadequate monitoring by sampling analyses. Consequently, there is a relatively low guarantee of product quality; further, off-specification fuels may be sold in the market. This paper proposes to strengthen governmental leadership by improving FQMS in terms of both the legal aspect and operational systems.